A Perspective on Digital Knowledge Representation in Materials Science and Engineering. Issue 6 (12th April 2022) - Bayerlein, Bernd; Hanke, Thomas; Muth, Thilo; Riedel, Jens; Schilling, Markus; Schweizer, Christoph; Skrotzki, Birgit; Todor, Alexandru; Moreno Torres, Benjami; Unger, Jörg F.; Völker, Christoph; Olbricht, Jürgen
Abstract : The amount of data generated worldwide is constantly increasing. These data come from a wide variety of sources and systems, are processed differently, have a multitude of formats, and are stored in an untraceable and unstructured manner, predominantly in natural language in data silos. This problem can be equally applied to the heterogeneous research data from materials science and engineering. In this domain, ways and solutions are increasingly being generated to smartly link material data together with their contextual information in a uniform and well‐structured manner on platforms, thus making them discoverable, retrievable, and reusable for research and industry. Ontologies play a key role in this context. They enable the sustainable representation of expert knowledge and the semantically structured filling of databases with computer‐processable data triples. Abstract : The Materials‐open‐Laboratory (Mat‐o‐Lab) project initiative aims to provide a collaborative environment for material science and engineering experts to digitize their research results and processes. The immediate goal is to enable data‐driven materials design and development by providing a unified framework for the creation and interchange of semantically structured scientific data. Artwork by Jens Riedel, owned by Bundesanstalt für Materialforschung und ‐prüfung (BAM).